Genotype and haplotype analysis of ABCB1 at 1236, 2677 and 3435 among systemic sclerosis patients - Małgorzata Barańska; Mariola Rychlik-Sych; Jadwiga Skrętkowicz; Michał Dudarewicz; Bożena Dziankowska-Bartkowiak; Jacek Owczarek; Elżbieta Waszczykowska (Taylor & Francis Group, 2017)
Systemic sclerosis (SSc) belongs to the group of systemic diseases of the connective tissue, which are characterized by a chronic autoimmune inflammatory process. P-glycoprotein, initially associated with the drug resistance in patients with cancer, becomes more and more often a subject of considerations in terms of its significance in the development of illnesses, including autoimmune diseases. The aim of the study was an attempt to answer the question whether there was a relationship between ABCB1 polymorphisms and morbidity of systemic sclerosis in a Polish population. The study was carried out in 61 patients with SSc and 100 healthy volunteers. Determination of polymorphisms C1236T and C3435T in ABCB1 was carried out with the PCR-RFLP (polymerase chain reaction - restriction fragment length polymorphism) method. The G2677T/A ABCB1 polymorphism was analysed with the allele-specific PCR method. No statistically significant differences were observed in the frequencies of ABCB1 genotypes and alleles between SSc patients and the control group. It was observed that haplotype 1236 C-2677 G-3435 T occurred in the group of patients with SSc statistically more frequently than in the group of healthy volunteers (25% vs. 15%; p = .032). Carriers of the haplotype demonstrated almost a twofold greater risk of SSc (OR = 1.85; p = .032). No statistically significant correlations for the other nine haplotypes were found. Presented results concerning the relationship of ABCB1 polymorphisms with susceptibility to systemic sclerosis are the first ones that were obtained in a Polish population. They imply that single nucleotide polymorphisms do not affect the risk for SSc, but the 1236 C-2677 G-3435 T haplotype might increase this risk.